If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = 0 Reorder the terms: -6 + 12x = 0 Solving -6 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 12x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = 0 + 6 12x = 0 + 6 Combine like terms: 0 + 6 = 6 12x = 6 Divide each side by '12'. x = 0.5 Simplifying x = 0.5
| 3x^2-6x+1= | | 24x^2-180x-96=0 | | 12(2x^2-15x-8)=0 | | 9b^2+24b+16=0 | | 2x^2+60y+162= | | 2=4-x | | 2=4-6 | | 4x-10=2x-2 | | 49w^2-16f^2=0 | | 4-x=-7 | | 4b^2+28bd+49d^2=0 | | 49m^2-112m+64=0 | | 4w^2+28w+49t^2= | | 7x+4=5-(4x-4) | | -7=2x+5 | | 25s-30s+9= | | m(19m+9)=10 | | (A+6)+(B+6)=C+6 | | 8n-(-2)/7=6 | | 9b^2-49= | | 100x^2-99x-99=0 | | 4f-6=2f+22 | | -9r+3t-8s-5r+12s+4t-t+5s-r= | | 2l-3=l+14 | | 16a^2-196=0 | | 30+11=2o+13 | | y=3/2+1 | | 49r^2-144=0 | | 10d+6=8d+24 | | 3.5x-2.5=15 | | -b-7b-b= | | 12c^3+39c^2-36c=0 |